A simple‐wave damping model for flexible marsh plants. Issue 12 (12th November 2021) - Zhang, Xiaoxia; Lin, Pengzhi; Nepf, Heidi
Abstract: Marsh plants are typically composed of leaves attached to a central stem. Both the leaves and the stem are flexible and contribute to wave attenuation. This study developed a model to predict wave damping within a marsh based on a simple representation of the wave‐induced drag on an individual, flexible marsh plant. Specifically, the drag force on the leaves and the stem was represented separately using a scaling law developed for an isolated plant element, and a sheltering coefficient was applied to account for drag reduction on the leaves due to the interaction among the leaves and stem. The wave damping model was validated against laboratory experiments. The model was also compared to measurements of wave dissipation made in the field.